Working with coaches and their teams in youth and collegiate sport in the USA: An interview with Dr Andy Gillham - Commentary - Strachan, L. (International Journal of Sports Science & Coaching, 2018)
My final reflection in this interview highlights the importance of positive development throughout youth and into emerging adulthood. The personal skills and experiences that youth amass in youth sport participation need to continue, as they enter post-secondary education. There is emerging research working to produce measures to examine sport experiences in university/collegiate sport. More needs to be explored in this realm, so that practitioners and researchers alike can get a better sense of the link between these two sport contexts (i.e., youth and collegiate).